Kajian Perancangan Model Pendampingan Perekonomian Masyarakat Desa Sentra Industri Batik Menggunakan Pendekatan Inkubasi Bisnis - Dinar Ari Prasetyo; Rullyana Puspitaningrum Mamengko (BULLET : Jurnal Multidisiplin Ilmu, 2022)
One of the National Priorities developed by the Indonesian Republic Government through the second phase of the Nawacita Program is to change the development priorities that were previously centered in urban areas and switch to development in rural and outer areas. This study was carried out for optimizing government policies in developing the village economy through several programs and financial incentives village (dana desa) so that it can provide maximum benefits for the welfare of the village community. This study designed an empowerment model of economic assistance for rural communities with case studies in batik industrial center village (in Gulurejo Village, Lendah, Kulon Progo). Implementation of this model is not only suitable for batik industrial center villages but also can be used for villages with economic potential through handicraft industry centers such as batik, apparel, leather, wood, paper, metal, and furniture. The result of this study is the adaptation of the business incubation model for the design of the empowerment model of economic assistance for the Village Community Center for the batik industrial center villages where there is three main activity in a business incubation model: Pre-Incubation, Main-Incubation, and After-Incubation. In its adaptation of the Economic Assistance Model for the Village Community Center for the Batik Industry, three main stages in this model are the preparation stage for one month, the implementation stage for about 6 months, and the post-stage implementation with one month period. In the preparation stage, there are several activities carried out including socialization, survey and mapping, recruitment, selection, and dissemination of preparation results. The implementation phase consists of training management/business with online and offline methods. The post-assistance stage is monitoring and evaluation, expanding networking, business scale up, and digitization